Developing a Web-based GIS Application for Earthquake Mapping - Boermel, Christian (The University of Edinburgh, 2012)
The fast technical progress of web-based GIS has enabled visualising complex geographical phenomena for the interested public. This research paper analyses the development of a global earthquake web map which allows the visualisation of significant seismic activity, in the context of geophysics, and the risk posed to local populations. The project is an extension of the World-Wide Earthquake Locator (WWEL) developed at the University of Edinburgh. Regarding the user features developed, a user-centric design approach (UCD) was taken to assess the user requirements of functionality and interface design. UCD analysis tools, which include surveys, persona and user journey analysis, and user usability testing, are also employed in the usability evaluation. The map application is based on the JavaScript client OpenLayers whose data handling capabilities have been particular examined. The earthquake data has been distinguished into “recent” and “historic”, whereby the former draws on USGS data feeds and the later links to a comprehensive database. Special focus has been put on the provision of contextual information. Data displaying volcano activity over varying time ranges, as well as tectonic plate boundaries, are utilised in order to aid the broader geophysical understanding. Emphasis has been put on the development of a layer depicting population density and poverty, allowing the user to achieve a more holistic picture of earthquake hazards.
Keywords: GIS; Earthquake; web-based GIS; mapping; World-Wide Earthquake Locator; WWEL; MSc Geographical Information Science; GIS